Silicon-carbon negative electrode material, preparation method thereof and soft package battery

CN122930867APending Publication Date: 2026-10-16SHAANXI JIANGFAN GUIZHI NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611085027.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本发明的目的在于克服上述现有技术的缺点,提供一种硅碳负极材料及其制备方法和软包电池,以解决现有技术中硅碳负极材料导电性差、体积膨胀大、循环稳定性不足的技术问题

Benefits of technology

本发明公开了一种硅碳负极材料,该材料在多孔碳核的外部设置有内外双包覆层结构,内层为导电子包覆层,外层为导电、导离子的改性聚合物层。所述内包覆层为Cu、Ag、Zn中的至少一种形成的高导电包覆层,外包覆层为改性聚合物层。在内包覆层中,硅颗粒作为活性物质起到储存锂离子作用,金属颗粒具有高导电性和良好的延展性,可以提供良好的电子传导性并缓解体积膨胀,通过这种独特的内外双包覆层结构设计,本发明制备的硅碳负极材料能够提供快速的离子、电子传输通道,从而提高材料的倍率性能。同时,高弹性的三维网络结构包覆层可以有效抑制硅碳负极材料的体积膨胀,提供良好的应力释放,防止颗粒破碎,避免粉化,弹性聚合物导电、导离子的结构组分设计使其在抑制膨胀的同时提高倍率性能、循环性能。该负极材料通过独特的双包覆层结构设计和材料选择,有效解决硅基负极材料存在的阻抗大、膨胀效应大等问题,显著提高硅碳负极的倍率性能和循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930867A_ABST
    Figure CN122930867A_ABST
Patent Text Reader

Abstract

The application discloses a kind of silicon-carbon negative electrode material and its preparation method and soft package battery, belong to lithium ion battery technical field;The silicon-carbon negative electrode material includes core, carbon layer, electron-conducting coating layer and outer layer modified polymer layer, the surface of core is covered with carbon layer, carbon layer is wrapped by electron-conducting coating layer, electron-conducting coating layer is wrapped by outer layer modified polymer layer;The main structure of core is porous carbon, and nano-silicon particles and nano-metal particles are distributed in porous carbon;Electron-conducting coating layer is composed of nano-metal particles, and outer layer modified polymer layer is composed of electric conductor, elastomer and lithium salt compound.This application constructs efficient electron and ion transmission channel by inside and outside double coating layer structure design, effectively inhibits volume expansion, significantly improves the rate performance and cycle stability of material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a silicon-carbon anode material, its preparation method, and a pouch cell. Background Technology

[0002] With the rapid development of electronic devices and electric vehicles, higher performance requirements are being placed on lithium-ion batteries. Silicon-based materials, with a theoretical specific capacity as high as 4200 mAh / g, far exceeding traditional graphite anode materials, are considered highly promising next-generation lithium-ion battery anode materials. However, silicon-based materials face many challenges in practical applications. First, silicon undergoes significant volume changes during lithium insertion and extraction, with an expansion rate reaching approximately 300%, leading to material structure damage, particle pulverization, and consequently, rapid capacity decay and poor cycle stability. Second, silicon's intrinsic electronic and ionic conductivity is relatively low, limiting the battery's rate performance and cycle performance.

[0003] To address these issues, one common approach is to composite silicon with porous carbon to form silicon-carbon anode materials, followed by carbon coating. The confinement effect of porous carbon and the buffering effect of the carbon layer can alleviate silicon volume expansion to some extent. However, existing coating structures and materials still have shortcomings and cannot fully meet the requirements of high-performance lithium-ion batteries for anode materials. For example, traditional single coating layers cannot simultaneously achieve efficient electron transport, ion transport, and effective suppression of volume expansion, resulting in a need for further improvement in the overall performance of the material. Patent CN 119008894 A discloses a method for preparing silicon-carbon materials with nano-copper-doped porous carbon. Copper doping improves the conductivity of porous carbon, thereby enhancing rate performance. However, because copper is doped in porous carbon, this method cannot form an effective conductive network structure between silicon particles; the conductive structure only exists at the interface between porous carbon and silicon particles, which has limited impact on performance improvement. Furthermore, the effect of a single coating layer structure is limited and cannot simultaneously address rate, expansion, and cycle performance. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a silicon-carbon anode material, its preparation method, and a pouch cell, so as to solve the technical problems of poor conductivity, large volume expansion, and insufficient cycle stability of silicon-carbon anode materials in the prior art.

[0005] To achieve the above objectives, the present invention employs the following technical solution: A silicon-carbon anode material includes, from the inside out, a core, a carbon layer, a conductive electron coating layer, and an outer modified polymer layer. The outer surface of the core is covered with a carbon layer, which is then encapsulated by the conductive electron coating layer, which is further encapsulated by the outer modified polymer layer. The core has a porous carbon structure containing nano-silicon particles and nano-metal particles. The conductive electron coating layer is composed of nano-metal particles, and the outer modified polymer layer is composed of a conductor, an elastomer, and a lithium salt.

[0006] A further improvement of the present invention is that: Preferably, the porous carbon is any one or more of coal-based porous carbon, biomass-based porous carbon, organic polymer-based porous carbon, or resin-based porous carbon.

[0007] Preferably, the nano-metal particles are a multi-element alloy composed of any one or more of Cu, Ag, or Zn.

[0008] Preferably, the conductor in the outer modified polymer layer is any one or more of a conductive polymer or a conductive nanofiller.

[0009] Preferably, the conductor includes at least one conductive nanofiller.

[0010] Preferably, the conductive polymer is at least one of polyaniline, polypyrrole, or polythiophene; and the conductive nanofiller is at least one of carbon nanotubes, graphene, carbon fibers, or conductive carbon black.

[0011] Preferably, the elastomer is at least one of polyurethane, nitrile rubber, or styrene-butadiene rubber.

[0012] Preferably, the lithium salt is at least one of Li2CO3, LiCl, LiFSI, LiBOB, or LiTFSI.

[0013] A method for preparing the above-mentioned silicon-carbon anode material includes: S1, through silane vapor deposition, nano-silicon particles are deposited in porous carbon, and acetylene is introduced to obtain a silicon-carbon semi-finished product with a carbon layer on the surface. S2, the silicon-carbon semi-finished product is placed in a metal salt solution, filtered under positive pressure to obtain the process product, and the process product is reduced at high temperature to obtain porous carbon loaded with nano-silicon particles and nano-metal particles. The outer surface of the porous carbon is wrapped with a conductive electron coating layer composed of nano-metal particles, which serves as the process silicon-carbon sample. S3 involves dissolving or dispersing a conductor, an elastomer, and a lithium salt in water, adding porous carbon with a deposited carbon layer, and then performing a polymerization reaction to obtain a silicon-carbon anode material coated with an outer modified polymer layer.

[0014] A pouch cell comprising the silicon-carbon anode material described in any one of the above-mentioned embodiments.

[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a silicon-carbon anode material with an inner and outer double-coating structure surrounding a porous carbon core. The inner layer is a conductive electron coating, and the outer layer is a conductive and ion-conducting modified polymer layer. The inner coating is a highly conductive coating formed from at least one of Cu, Ag, and Zn, while the outer coating is a modified polymer layer. In the inner coating, silicon particles act as the active material, storing lithium ions. The metal particles possess high conductivity and good ductility, providing excellent electronic conductivity and mitigating volume expansion. Through this unique inner and outer double-coating structure design, the silicon-carbon anode material prepared by this invention can provide a rapid ion and electron transport channel, thereby improving the rate performance of the material. Simultaneously, the highly elastic three-dimensional network structure coating effectively suppresses the volume expansion of the silicon-carbon anode material, providing good stress release, preventing particle breakage, and avoiding pulverization. The conductive and ion-conducting structural components of the elastic polymer further enhance rate and cycle performance while suppressing expansion. This anode material, through its unique double-coating structure design and material selection, effectively solves the problems of high impedance and large expansion effect of silicon-based anode materials, and significantly improves the rate performance and cycle stability of silicon-carbon anodes.

[0016] In the application of this silicon-carbon anode material, the conductive electron layer formed by the nano-metal particles possesses an excellent electronic conduction network, significantly improving the lithium-ion diffusion rate and charge transport efficiency, thus exhibiting good rate performance. The nano-metal particles themselves have good electronic conductivity, and during the initial lithiation process, they can form a rapidly conducting Li-ion network. X - Metal alloys accelerate lithium-ion diffusion, further leading to the formation of Li₂ with high ionic conductivity. X Ag and other alloys are distributed around silicon particles, forming a good ion transport pathway and accelerating ion transport. Attached Figure Description

[0017] Figure 1 Here is a SEM image of the sample from Example 1; Figure 2 The diagram shows the cyclic performance of Example 1 and the comparative example. Detailed Implementation

[0018] The present invention will now be described in further detail with reference to the accompanying drawings: To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0019] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the specific range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if 60 is listed for a specific parameter... 120 and 80 The range of 110 is understood to be 60. 110 and 80 The range of 120 is also expected. Furthermore, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4, and 5 are listed, then the following ranges are all expected: 1 3.1 4.1 5.2 3, 2 4 and 2 5. In this application, unless otherwise stated, the numerical range "a" "b" represents a shortened representation of any combination of real numbers from a to b, where both a and b are real numbers. For example, the numerical range "0" represents a combination of real numbers from a to b. "5" indicates that all "0"s have been listed in this article. All real numbers between "5" and "0". "5" is simply an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer greater than or equal to 2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0020] In the description of this application, it should be noted that, unless otherwise stated, "a plurality of" means two or more; the terms "upper," "lower," "left," "right," "inner," and "outer," etc., indicating orientation or positional relationships, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on this application. Furthermore, the terms "first," "second," and "third," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance. "Vertical" is not vertical in the strict sense, but within the allowable tolerance range. "Parallel" is not parallel in the strict sense, but within the allowable tolerance range.

[0021] The directional terms used in the following description refer to the directions shown in the figures and are not intended to limit the specific structure of this application. It should also be noted in the description of this application that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "joining" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a direct connection or an indirect connection through an intermediate medium. Those skilled in the art can understand the specific meaning of the above terms in this application based on the specific circumstances.

[0022] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0023] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B".

[0024] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0025] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0026] To achieve the above objectives, this invention provides a silicon-carbon anode material comprising, from the inside out, a core, a carbon layer, a conductive electron coating layer, and an outer modified polymer layer. The outer surface of the core is covered by a carbon layer, which is then encapsulated by the conductive electron coating layer, which is further encapsulated by the outer modified polymer layer. The core has a porous carbon structure containing nano-silicon particles and nano-metal particles. The conductive electron coating layer is composed of metal particles, and the outer modified polymer layer is composed of a conductor, an elastomer, and a lithium salt.

[0027] This silicon-carbon anode material contains highly conductive nano-metal particles within the porous carbon and also serves as a conductive coating layer. Specifically, the porous carbon, acting as the core framework matrix, utilizes its abundant pore structure to provide space for the nano-silicon particles, thus physically limiting the volume expansion of silicon during lithium intercalation. Simultaneously, the porous carbon itself constructs a basic long-range conductive network. The nano-silicon particles distributed within the porous carbon, as the primary electrochemical active material, undertake the core function of storing lithium ions. The nano-metal particles distributed within the porous carbon play a crucial role in enhancing internal conductivity. They fill the gaps between the porous carbon and the nano-silicon particles, effectively reducing the contact resistance between the active material and the carbon framework, and improving the overall electron mobility of the core. The carbon layer covering the surface of the porous carbon is a thin layer that suppresses the expansion of the entire porous carbon. This porous carbon is not a continuous layer, allowing pores or parts of the surface to be exposed. The conductive electron coating layer, composed of nano-metal particles, is located between the core and the outer modified polymer layer. Its main function is to construct an efficient interfacial electron transport channel. Since the porous carbon on the core surface may have uneven conductivity or local defects, directly coating the polymer layer could lead to excessively high interfacial impedance. By constructing a dense coating layer composed of highly conductive nano-metal particles in situ on the core surface, not only is the electron tunneling barrier between the core and the outer layer significantly reduced, but a good adhesion substrate is also provided for the outer modified polymer layer, ensuring rapid longitudinal electron transport throughout the electrode material. The outer modified polymer layer establishes a continuous electron conduction path, compensating for the shortcomings of traditional polymer insulation. The elastomer endows the outer layer with excellent flexibility and mechanical strength, enabling it to adapt to the volume breathing effect of the core during battery cycling. It absorbs stress through its own elastic deformation, preventing material pulverization or coating layer cracking. In-situ doping of lithium salt gives the polymer layer ionic conductivity, opening a rapid channel for lithium ions to diffuse from the electrolyte to the core and reducing interfacial charge transfer impedance. This anode material can greatly improve the poor conductivity of silicon-based anodes and increase electron mobility, thereby improving their rate performance and cycle performance. At the same time, the outer high-elasticity polymer coating layer can provide good toughness, prevent particle breakage and pulverization, and improve cycle stability.

[0028] The carbon layer has a coating thickness of 1-10 nm, preferably 1-2 nm. The conductive electron coating layer and the modified polymer layer have coating thicknesses of 1-50 nm, preferably 2-10 nm.

[0029] In some embodiments of the present invention, the porous carbon is any one or more of coal-based porous carbon, biomass-based porous carbon, organic polymer-based porous carbon, or resin-based porous carbon. The porous carbon matrix is ​​selected from porous carbon materials with high specific surface area, well-developed pore structure, and good conductivity. On the one hand, it can buffer the volume expansion of nano-silicon particles through the pore space; on the other hand, it can construct initial conductive pathways and improve the structural stability of the material.

[0030] Specifically, porous carbon can be any one or more of coal-based porous carbon, biomass-based porous carbon, or resin-based porous carbon.

[0031] The nano-metal particles are conductive nano-metal particles, and are multi-element alloys composed of one or more of Cu, Ag, or Zn, with copper being preferred. Specifically, copper (Cu) is the preferred basic component for constructing fast electron transport networks due to its extremely high intrinsic electronic conductivity, and can significantly reduce the ohmic impedance of the material. Zinc (Zn), in addition to having good conductivity, can also undergo alloying reactions with lithium or form stable metal silicide interfaces with silicon during electrochemical processes, thereby further improving the interfacial wettability between the nano-silicon particles and the carbon framework and enhancing structural stability. When two or more metals are used to form a multi-element alloy, such as a Cu-Zn alloy, the lattice distortion effect and electron cloud rearrangement between different metal atoms can produce a synergistic enhancement effect. This not only improves the mechanical ductility of the metal phase while maintaining high conductivity, making it more adaptable to the drastic volume changes of silicon-based materials during cycling, but also optimizes the interfacial bonding force between the metal particles and the porous carbon and outer polymer layer by adjusting the alloy component ratio.

[0032] The size of the nano-metal particles is 90 nm to 1 μm. If the size of the nano-metal particles is less than 90 nm, their specific surface area is too large, and their surface energy is extremely high. During high-temperature reduction and subsequent battery cycling, they are prone to aggregation or excessive oxidation, leading to a loss of effective conductive area. Furthermore, excessively small particles are difficult to form continuous long-range conductive pathways within the porous carbon pores. Conversely, if the size exceeds 1 μm, the metal particles will occupy too much pore space, crowding out the loading sites of the nano-silicon, resulting in a decrease in the overall specific capacity of the material. At the same time, the volume expansion stress concentration effect of large-sized particles is significant, easily piercing the outer modified polymer layer or causing the core structure to collapse. The nano-silicon particles have a particle size of 1-10 nm, with approximately 2 nm being preferred.

[0033] As a preferred embodiment, the nano-metal particles in the silicon-carbon anode material are formed by high-temperature reduction of their corresponding metal salts.

[0034] The outer elastic polymer coating layer comprises the following materials: a conductor, an elastomer, and a lithium salt, with a mass ratio of (40-60):(30-50):(1-20), preferably 50:40:10.

[0035] The conductor in the outer modified polymer layer is any one or more of a conductive polymer or a conductive nanofiller, and the polymer conductor is polymerized from its monomers. Specifically, when a conductive polymer is used as the conductor, its advantage is that it can form a uniform, dense and continuous film on the core surface through in-situ polymerization and other methods. This film not only provides electron channels, but also acts as a binder to enhance the interfacial bonding force between the outer layer and the conductive electron coating layer. Moreover, the flexibility of the polymer chain segments helps to adapt to the volume changes of silicon-based materials. When a conductive nanofiller is used as the conductor, its advantage is that it has higher intrinsic conductivity and a more stable conductive network structure. It is not easily affected by the rearrangement or breakage of polymer chain segments during electrochemical cycling and can maintain low impedance characteristics over a long period of time.

[0036] As a preferred embodiment, the conductive polymer is at least one of polyaniline, polypyrrole, or polythiophene; preferably, it is polypyrrole, whose polymer conductor is polymerized from its monomers and has good biocompatibility and relatively stable doping / dedoping behavior during electrochemical cycling.

[0037] As a preferred embodiment, the nanofiller is selected from at least one of carbon nanotubes, graphene, carbon fibers, and conductive carbon black, with carbon nanotubes being the preferred choice.

[0038] In a more preferred embodiment, the conductor includes at least one conductive nanofiller. That is, when the conductive polymer is used alone, at least one conductive nanofiller is added to ensure conductivity. While conductive polymers can form a uniform coating film and provide a certain level of electronic conductivity through in-situ polymerization, during the repeated drastic volume expansion and contraction caused by lithium insertion and extraction in silicon-carbon anode materials, pure polymer segments are prone to fatigue fracture, rearrangement, or peeling from the surface of the active material. This leads to the gradual failure of the originally continuous conductive pathway, macroscopically manifested as a significant increase in battery internal resistance with increasing cycle count and accelerated capacity retention decay. By forcibly introducing at least one conductive nanofiller into the conductor, the excellent intrinsic conductivity and unique geometric morphology of the nanofiller (such as a one-dimensional tubular structure with a high aspect ratio or a two-dimensional sheet structure with a high specific surface area) can be utilized to construct a conductive channel independent of the polymer segments within the outer modified polymer layer. This framework network has a low permeation threshold and high structural redundancy. Even if the polymer matrix undergoes local deformation or microcracks under stress, the nanofillers can still maintain effective physical contact or tunneling effect, ensuring the integrity and durability of the electron transport pathway.

[0039] In a preferred embodiment, the outer modified polymer layer uses a combination of polypyrrole and carbon nanotubes as a conductor. This combination is not a simple physical mixture, but rather an organic-inorganic interpenetrating network structure formed through an in-situ polymerization process. Specifically, carbon nanotubes are first uniformly dispersed in an aqueous solution containing pyrrole monomers. Utilizing the π-π interaction between the π electrons on the surface of the carbon nanotubes and the pyrrole monomers, the monomer molecules are pre-adsorbed and orderly arranged on the surface of the carbon nanotubes. Subsequently, an oxidant is added to initiate the polymerization reaction, allowing polypyrrole to grow directly on the surface of the carbon nanotubes in situ and form a dense coating. This unique structural design brings multiple technological advantages: Firstly, carbon nanotubes, acting as a rigid conductive framework, permeate the entire polymer layer. Even if the polypyrrole matrix experiences microcracks or chain fatigue during repeated volume expansion and contraction of the silicon-based core, the carbon nanotube network can still maintain the integrity of the electron transport pathway, avoiding the impedance surge problem common in purely conductive polymers during the later stages of cycling. Secondly, the in-situ grown polypyrrole layer not only provides electron conduction itself but also acts as an interfacial compatibilizer between the carbon nanotubes and the elastomer matrix, enhancing the bonding force between the inorganic filler and the organic matrix and preventing the nanofiller from agglomerating or detaching during long-term cycling. Furthermore, polypyrrole itself has a certain degree of ion permeability, which, combined with the lithium salt doped within the layer, further promotes the rapid diffusion of lithium ions in the outer layer, achieving highly efficient dual electron and ion transport.

[0040] As a preferred embodiment, the elastomer includes at least one of polyurethane, nitrile rubber, and styrene-butadiene rubber, with polyurethane being the preferred choice. The polyurethane molecular chain consists of alternating soft and hard segments. This microphase separation structure combines the high elasticity of rubber with the high strength of plastics: the soft segments (typically polyether or polyester polyol) provide chain mobility, imparting low modulus and high elongation to the material, allowing it to adapt to the intense volumetric breathing of the silicon-based core; the hard segments (formed from isocyanates and chain extenders) form physical crosslinking points through hydrogen bonding and crystallization, providing necessary mechanical support and creep resistance, preventing permanent plastic deformation of the outer layer after repeated deformation. Furthermore, the urethane bonds in the polyurethane molecule exhibit excellent resistance to carbonate electrolytes commonly used in lithium-ion batteries, resisting swelling or degradation, thus ensuring the structural integrity and interfacial stability of the outer modified polymer layer under long-term immersion in the electrolyte environment.

[0041] In this embodiment, the mass percentage of the elastomer in the outer modified polymer layer is preferably controlled between 30% and 50%. This ratio range is determined based on the impact on the balance between mechanical buffering performance and ion and electron transport performance. If the elastomer content is less than 30%, the overall modulus of the outer modified polymer layer is too high, and the flexibility is insufficient, making it difficult to fully dissipate the huge expansion stress generated by the silicon-based core in the deep lithium-intercalation state, which can easily lead to cracking and failure of the coating layer. Conversely, if the elastomer content exceeds 50%, although the buffering capacity is further enhanced, since the elastomer itself is a poor conductor of ions and electrons, an excessively high proportion will significantly dilute the effective concentration of the conductor and lithium salt, resulting in a significant decrease in the ionic and electronic conductivity of the outer layer, thereby increasing the polarization resistance of the battery and deteriorating the rate performance and capacity utilization. Therefore, maintaining the elastomer content in the range of 30% to 50% can ensure that the outer layer has sufficient elastic deformation capacity to suppress electrode expansion, while maintaining an efficient charge transport channel, achieving the best synergy between mechanical protection and electrochemical performance.

[0042] As a preferred embodiment, the lithium salt is selected from at least one of Li₂CO₃, LiCl, LiFSI, LiBOB, and LiTFSI, with LiFSI being the preferred choice. The selection of the lithium salt fully considers its synergistic effect with other components in the outer modified polymer layer and its positive impact on the stability of the solid electrolyte interphase (SEI) film. On the one hand, organic lithium salts such as LiFSI, LiTFSI, and LiBOB have good compatibility with conductive polymers and elastomers, and can be uniformly dispersed within the matrix during polymerization, avoiding phase separation or crystallization caused by excessively high local concentrations, thus ensuring the uniformity and mechanical integrity of the outer layer structure. On the other hand, these lithium salts preferentially undergo reduction and decomposition before solvent molecules in the early stages of electrochemical cycling, participating in the formation of a dense SEI film rich in inorganic components such as LiF and Li₂S. This SEI film derived from lithium salts not only has high ionic conductivity and low electronic conductivity, effectively suppressing continuous side reactions of the electrolyte on the core surface, but also possesses excellent mechanical strength and flexibility, enabling it to adapt to the volumetric breathing of silicon-based materials during cycling without breaking.

[0043] A second aspect of the present invention provides a method for preparing a low-expansion, high-rate silicon-carbon anode material, comprising the following steps: S1, porous carbon is placed in a CVD furnace for silane vapor deposition to obtain a silicon-carbon core, and then acetylene is introduced to coat the carbon layer to obtain a silicon-carbon semi-finished product; in this process, silicon is vapor-deposited into the porous carbon to obtain silicon-carbon sample 1, silicon forms nano-silicon inside the pores of the porous carbon and on the surface of the porous carbon, and then a carbon layer is coated on the outside of the silicon-carbon core with acetylene to obtain a silicon-carbon semi-finished product substrate. In this embodiment, the porous carbon matrix is ​​placed in a chemical vapor deposition furnace and heated to 500-600°C, preferably 550°C, under an inert atmosphere. Silane gas is introduced at a certain flow rate to carry out the deposition reaction, and the holding time is 300-500 min, preferably 400 min, to allow the silicon source to fully diffuse into the pores inside the porous carbon and decompose and deposit in situ to form nano-silicon particles. Subsequently, acetylene gas is introduced for carbon coating treatment, and the gas is introduced continuously for 40-80 min, preferably 60 min, to form a thin carbon layer on the surface of the nano-silicon particles and the outer surface of the porous carbon, thus obtaining a silicon-carbon semi-finished product. The carbon layer can reduce expansion. However, since the thickness of this thin carbon layer is relatively thin, it only covers a small amount of the surface of the porous carbon and is a discontinuous carbon layer. After this step, the surface of the porous carbon is still partially exposed, allowing the subsequent metal salt solution to still penetrate into the interior of the porous carbon.

[0044] In step S2, the metal salt is dissolved in deionized water. Then, the silicon-carbon sample from step S1 is dispersed in the metal salt aqueous solution. After stirring evenly, positive pressure filtration is performed to remove the remaining solution. In this process, by combining impregnation with positive pressure filtration, the metal salt solution can be precisely introduced into the pores inside the porous carbon using capillary force. At the same time, an appropriate amount of metal salt precursor is retained on the outer surface of the particles, laying the material basis for the subsequent formation of an internal and external bimetallic structure.

[0045] Preferably, the metal salt is a metal salt corresponding to different metal elements, such as chloride salts, nitrate salts, such as CuCl2, Cu(NO3)2, ZnCl2, CuSO4, ZnSO4, etc.

[0046] The concentration of the metal salt is 0.1% to 20%, preferably 10%. The concentration of the metal salt affects the number of nano-metal particles in the final core. If the number is too small, an effective conductive network structure cannot be constructed, and if the number is too large, the material capacity will be reduced. The mass ratio of the metal salt solution to the silicon-carbon substrate is 0.5 to 2:1, preferably 1.5:1.

[0047] The silicon-carbon sample is then subjected to high-temperature reduction in a heating furnace to obtain a silicon-carbon sample coated with a conductive metal layer. The reduction temperature is 500~800℃, and the reduction time is 1~5h. The preferred reduction temperature is 600℃ for 2 hours. The reduction method is carbothermal reduction or H2 reduction, preferably H2 reduction, with a flow rate of 35mL / min. Through this step, the metal salt inside the porous carbon is reduced to metal particles. Simultaneously, a metal layer composed of nano-metal particles is formed on the surface of the porous carbon, serving as a conductive coating layer. This step forms the silicon-carbon sample.

[0048] In this step, the metal salt precursors adsorbed inside and on the surface of the porous carbon are reduced in situ to elemental metals. Due to the difference between surface tension and sintering driving force, the metal located inside the pores tends to form dispersed nanoparticles, which enhance internal conductivity; while the metal located on the outer surface tends to agglomerate to form a dense, continuous coating layer, i.e., a conductive electron coating layer.

[0049] S3: The conductor, elastomer, and lithium salt are added to an aqueous solution at a mass ratio of (40-60):(30-50):(1-20) and mixed thoroughly. Then, the silicon-carbon sample prepared in S3 is added and mixed thoroughly. Ammonium persulfate is added and polymerized at 0-5℃ for 4-8 hours to obtain a silicon-carbon sample coated with a conductive and ion-conducting elastic polymer. The amount of ammonium persulfate added as an initiator is the same as the molar amount of the monomer forming the conductor. Specifically, polyaniline is formed through the monomer aniline, polypyrrole through the monomer pyrrole, and polythiophene through the monomer thiophene.

[0050] In this process, low-temperature polymerization conditions are crucial for controlling the growth rate of conductive polymers such as polypyrrole. These conditions effectively suppress excessive crosslinking and disordered stacking, promoting the formation of dense, uniform, and highly flexible films on the surface of the silicon-carbon sample. Simultaneously, carbon nanotubes and lithium salts are in-situ embedded into the polymer matrix during polymerization, forming an elastic network structure with dual electron-ion conductivity.

[0051] A third aspect of this invention provides an application of a low-expansion, high-rate silicon-carbon anode material for preparing pouch cells. In this process, the silicon-carbon anode material, conductive carbon black, and sodium carboxymethyl cellulose (CMC) binder are first mixed at a mass ratio of 96:1:3. Deionized water is added, and the mixture is stirred at 2500 rpm for 30 minutes in a homogenizer to form a uniform slurry. The slurry is then sieved and uniformly coated onto a copper foil current collector, placed in a 90°C vacuum drying oven for 2 hours, and then rolled and cut to obtain the anode sheet. Finally, in a glove box, a lithium metal sheet is used as the counter electrode, along with a separator, electrolyte, and gaskets, to assemble a coin cell for testing, or a pouch cell can be directly prepared using an aluminum-plastic film encapsulation process.

[0052] Preferably, the battery includes secondary batteries such as sulfide solid-state batteries and liquid batteries.

[0053] The following description, in conjunction with specific embodiments, provides further details.

[0054] Example 1 S1. Weigh 2 kg of porous carbon and place it in a CVD furnace, then introduce nitrogen gas. Control the nitrogen flow rate at 14.5 L / min, raise the furnace temperature to 550℃, and introduce silane at a flow rate of 5 L / min for 400 min to obtain a silicon-carbon semi-finished substrate. Then, introduce acetylene gas at a flow rate of 4 L / min for 60 min to obtain a silicon-carbon semi-finished product with a carbon layer.

[0055] S2: Prepare a copper chloride solution at 10% of the mass of the silicon-carbon semi-finished substrate. Add the copper salt solution to the silicon-carbon semi-finished substrate from S1 at a mass ratio of 1.3:1. Stir for 2 hours, then filter under positive pressure to remove excess copper salt solution. Then place the sample in a furnace at 600℃ and reduce it with hydrogen for 2 hours to obtain the modified silicon-carbon sample.

[0056] S3. Pyrrole monomer, polyurethane, carbon nanotubes, and LiFSI were added to an aqueous solution and mixed thoroughly. The mass ratio of pyrrole monomer, polyurethane, carbon nanotubes, and LiFSI was 49:40:1:10, and the total mass fraction of all substances added to the water was 8%. Then, the silicon-carbon sample prepared in S3 was added, and after stirring thoroughly, ammonium persulfate was added. The mixture was then polymerized at a low temperature of 0-5℃ for 6 hours to obtain a conductive and ion-conducting elastic polymer-coated silicon-carbon sample. The SEM image of the prepared sample is shown below. Figure 1 As shown.

[0057] Example 2 Unlike Example 1, in Example 2 the concentration of copper chloride solution in S2 is 20%, and the remaining steps are the same as in Example 1.

[0058] Example 3 Unlike Example 1, in Example 3 the concentration of copper chloride solution in S2 is 0.1%, and the remaining steps are the same as in Example 1.

[0059] Example 4 In this embodiment, the mass ratio of copper salt solution to silicon-carbon semi-finished substrate is 0.5:1, and the remaining steps are the same as in Example 1.

[0060] Example 5 In this embodiment, the mass ratio of copper salt solution to silicon-carbon semi-finished substrate is 2:1, and the remaining steps are the same as in Example 1.

[0061] Example 6 In this embodiment, the reduction temperature is 500℃, the reduction time is 5h, and the remaining steps are the same as in Embodiment 1.

[0062] Example 7 In this embodiment, the reduction temperature is 800℃, the reduction time is 1 hour, and the remaining steps are the same as in Embodiment 1.

[0063] Comparative Example 1 S1, 2 kg of porous carbon was weighed and placed in a CVD furnace, and then nitrogen gas was introduced. The nitrogen flow rate was controlled at 14.5 L / min, the furnace temperature was raised to 550 °C, silane was introduced at a flow rate of 5 L / min and held for 400 min, and then acetylene gas was introduced at a flow rate of 4 L / min for 60 min to obtain a silicon-carbon sample. In this comparative example, neither nano-metal particle doping nor outermost elastic polymer coating was performed.

[0064] Comparative Example 2 Unlike Example 1, Comparative Example 2 does not perform the S4 polymer coating step, but the remaining steps are the same. The final material includes a core, a carbon layer and a conductive electron coating layer arranged sequentially from the inside out. The porous carbon contains nano-silicon particles and nano-metal particles.

[0065] Comparative Example 3 Unlike Example 1, Comparative Example 3 did not perform the S2 copper salt solution doping step or the thermal reduction process. The remaining steps were the same. The final material was a modified polymer coating layer directly coated on the outside of the porous carbon core. The porous carbon core contained no nano-metal particles, only silicon particles.

[0066] Battery fabrication and performance testing Silicon-carbon sample, conductive carbon black, and binder CMC were weighed in a mass ratio of 96:1:3, then deionized water was added and the mixture was homogenized using a homogenizer at 2500 rpm for 30 minutes. The slurry was then sieved and evenly coated onto copper foil, and dried in a 90℃ vacuum drying oven for 2 hours. The electrode sheets were then rolled and cut into circular shapes. Finally, in a glove box, a coin cell was assembled with a lithium metal sheet as the counter electrode, along with the prepared electrode sheets, separator, and gasket. The initial charge-discharge capacity, initial coulombic efficiency, and initial expansion rate were obtained at a current density of 0.1C and a voltage range of 0.005~1.5V. Capacity retention was obtained after 200 cycles at 0.5C. Rate performance was obtained by cycling at 0.1C, 0.5C, 1C, 2C, and 3C for 5 cycles each, and finally at 0.1C for 5 cycles.

[0067] Table 1. Performance test results of the examples and comparative examples:

[0068] As shown in Table 1, the capacity retention rates of Examples 1-3 are significantly higher than those of Comparative Examples 1-3 compared to Comparative Examples 1-3. Simultaneously, the initial expansion rate of the electrodes in Examples 1-3 is significantly lower than that in Comparative Examples 1-3. The silicon-carbon composite material with an inner and outer double-coating structure provided in Example 1 exhibits an initial reversible capacity of 1845.6 mAh / g, an initial coulombic efficiency of 94.58%, and retains 85.9% capacity after 200 cycles, demonstrating excellent cycling performance. Furthermore, thanks to the elastic, conductive, and ion-conducting outer coating structure, the initial expansion rate of the electrode in Example 1 (36.15%) is significantly lower than that in Comparative Example 2, which lacks a coating structure. Figure 2 The graph shows a comparison of the rate performance of Example 1 and Comparative Example 1. The results indicate that the double-coating structure formed by copper metal particles and a conductive, ion-conducting polymer exhibits superior rate performance, maintaining a capacity of 1587 mAh / g (capacity retention of 85.52%) at 3C high rates, while Comparative Example 1, without the double-coating structure, only achieves a capacity of 1290 mAh / g (capacity retention of 68.23%) at 3C high rates. The inner copper coating layer possesses excellent conductivity, and its doping in the silicon-carbon semi-finished substrate can construct efficient electron transport channels, reducing electron transport impedance. The outer polymer coating layer can limit volume expansion during cycling, improving cycling performance. Furthermore, conductive polypyrrole and carbon nanotubes can further enhance the electron transport efficiency of the material, while lithium salt doping endows the polymer layer with ion conductivity, effectively reducing the diffusion resistance of lithium ions at the material interface. The elastomer polyurethane provides good flexibility and elasticity, acting as a buffer when the silicon-based core expands, reducing internal stress and minimizing the material's expansion effect.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A silicon-carbon anode material, characterized in that, The device comprises, from the inside out, a core, a carbon layer, a conductive electron coating layer, and an outer modified polymer layer. The outer surface of the core is covered by a carbon layer, which is then encased by the conductive electron coating layer, which is further encased by the outer modified polymer layer. The core has a porous carbon structure containing nano-silicon particles and nano-metal particles. The conductive electron coating layer is composed of nano-metal particles, and the outer modified polymer layer is composed of a conductor, an elastomer, and a lithium salt.

2. The silicon-carbon anode material according to claim 1, characterized in that, The porous carbon is any one or more of coal-based porous carbon, biomass-based porous carbon, organic polymer-based porous carbon, or resin-based porous carbon.

3. The silicon-carbon anode material according to claim 1, characterized in that, The nano-metal particles are multi-element alloys composed of any one or more of Cu, Ag, or Zn.

4. The silicon-carbon anode material according to any one of claims 1-3, characterized in that, The conductor in the outer modified polymer layer is any one or more of a conductive polymer or a conductive nanofiller.

5. The silicon-carbon anode material according to claim 4, characterized in that, The conductor includes at least one conductive nanofiller.

6. The silicon-carbon anode material according to claim 4, characterized in that, The conductive polymer is at least one of polyaniline, polypyrrole, or polythiophene; the conductive nanofiller is at least one of carbon nanotubes, graphene, carbon fibers, or conductive carbon black.

7. The silicon-carbon anode material according to any one of claims 1-3, characterized in that, The elastomer is at least one of polyurethane, nitrile rubber, or styrene-butadiene rubber.

8. The silicon-carbon anode material according to any one of claims 1-3, characterized in that, The lithium salt is at least one of Li₂CO₃, LiCl, LiFSI, LiBOB, or LiTFSI.

9. A method for preparing the silicon-carbon anode material according to claim 1, characterized in that, include: S1, through silane vapor deposition, nano-silicon particles are deposited in porous carbon, and acetylene is introduced to obtain a silicon-carbon semi-finished product with a carbon layer on the surface. S2, the silicon-carbon semi-finished product is placed in a metal salt solution, filtered under positive pressure to obtain the process product, and the process product is reduced at high temperature to obtain porous carbon loaded with nano-silicon particles and nano-metal particles. The outer surface of the porous carbon is wrapped with a conductive electron coating layer composed of nano-metal particles, which serves as the process silicon-carbon sample. S3 involves dissolving or dispersing a conductor, an elastomer, and a lithium salt in water, adding porous carbon with a deposited carbon layer, and then performing a polymerization reaction to obtain a silicon-carbon anode material coated with an outer modified polymer layer.

10. A pouch battery, characterized in that, Includes the silicon-carbon anode material as described in any one of claims 1-8.

Citation Information

Patent Citations

  • Copper-doped porous carbon material, silicon-carbon composite material and application thereof

    CN119008894A